Prenatal Diagnosis of Isolated Lissencephaly by Ultrasonography and Magnetic Resonance Imaging: A Case Report - Kütük, Mehmet Serdar; Dolanbay, Mehmet; Özgün, Mahmut Tuncay; Akgün, Hülya; Yıkılmaz, Ali (Gynecology Obstetrics & Reproductive Medicine, 2014)
We present the abnormal sonographic findings in the brain of a 26-week fetus, which increased the suspicion of isolated lissencephaly. The woman had a history of prednisolone use in early pregnancy, and conceived with copper containing intra uterine device. Fetal magnetic resonance imaging and ultrasonography revealed hypoplastic cerebral parenchyma, and cortical agyria suggesting lissencephaly. Cordocentesis showed a normal 46, XY karyotype, and no deletion of chromosome 17 was detected. Post-mortem examination of the fetus confirmed prenatal US and MRI findings. Early detection of fetal microcephaly can be a sign of lissencephaly and need to be evaluated carefully with fetal MRI, and US.